2017
DOI: 10.1007/s10886-017-0859-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ferulic Acid with Glutathione S-Transferase and Carboxylesterase Genes in the Brown Planthopper, Nilaparvata lugens

Abstract: Plant phenolics are crucial defense phytochemicals against herbivores and glutathione S-transferase (GST) and carboxylesterase (CarE) in herbivorous insects are well-known detoxification enzymes for such xenobiotics. To understand relationship between a plant phenolic and herbivore GST or CarE genes, we evaluated the relationship between a rice phenolic ferulic acid and resistance to brown planthopper (BPH, Nilaparvata lugens), and investigated the interaction of ferulic acid with GST or CarE genes in BPH. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…We found that after treatment at 41°C for 1 h, expression of GSTs was significantly up-regulated in the heat-acclimated larvae, compared to the unacclimated larvae. Glutathione S-transferase (GST) is a family of detoxification enzymes in herbivorous insects [57]. The upregulation of oxidoreductase activity may effectively remove the accumulation of toxic substances induced by heat stress, and consequently improve the ability of larvae to tolerate the higher temerpature and slowly develop heat acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that after treatment at 41°C for 1 h, expression of GSTs was significantly up-regulated in the heat-acclimated larvae, compared to the unacclimated larvae. Glutathione S-transferase (GST) is a family of detoxification enzymes in herbivorous insects [57]. The upregulation of oxidoreductase activity may effectively remove the accumulation of toxic substances induced by heat stress, and consequently improve the ability of larvae to tolerate the higher temerpature and slowly develop heat acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we initially focused on studying the relationship of Orco with rice plants using RNAi in planthoppers combined with behavioral tests. RNAi is highly effective in rice planthoppers for functional study against insecticide‐resistance genes, trehalose, chitin biosynthesis pathway genes, vitellogenin receptors, sugar transporter genes and wing morph genes using synthetic double strand RNA (dsRNA). Because of the high identity level among the Orco genes in the three planthoppers, we were able to use only one pair of synthetic siRNAs to successfully and simultaneously inhibit >50% of the mRNA expression levels of the three Orco genes 48 h after injection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chlorogenic acids in chrysanthemum (Dendranthema grandiflora (Ramat.) effectively defend against thrips [34], pisatin (flavonoid) deters pea-aphid (Acyrthosiphon pisum Harris) in pea [35] (Table 1), and ferulic acid in rice impart resistance against brown planthopper (Nilaparvata lugens Stål) [36] to name a few. Increase in phenolic acids and flavonoids, especially quercetin has also been observed in white cabbage (Brassica oleraceae L. var.…”
Section: Classificationmentioning
confidence: 99%